THE EFFECTIVENESS OF IMPLEMENTING THE VILLAGE FINANCIAL SYSTEM (SISKEUDES) IN IMPROVING THE ACCOUNTABILITY OF VILLAGE FINANCIAL REPORTS (VILLAGE CASE STUDY OENIF AND TUNFEU VILLAGE NEKAMESE DISTRICT KUPANG DISTRICT) - Agusta Amanda Wulandari; Fransiscus Nicodemus Naiola (SEAN Institute, 2023)
Study This Purposeful For makes it easier in management finance village , government village together with BPKP to develop application called Village Financial System ( Siskeudes ) . Siskeudes made referring to the Minister of Home Affairs Regulation Number 113 of 2014. Expected with exists application This is accountability on report finance can materialized as well as increasing effectiveness and efficiency . Research objectives This is For analyze application Siskeudes in Oenif Village and Tunfeu Village and know is its use Already in accordance with Minister of Home Affairs Regulation Number 113 of 2014. Type of research used is study descriptive qualitative with approach studies case . Data obtained with method practice direct interviews , observations and documentation in Oenif Village and Tunfeu Village . Data obtained in the form of primary and secondary data . Primary data was obtained researcher with method interview direct with source . Meanwhile secondary data in the form of data that has been documented in Oenif Village and Tunfeu Village like structure organization , history short and report finance . Research results show that application Siskeudes really helped Oenif Village and Tunfeu Village especially in four part management finance village ie implementation , administration , reporting and accountability.